Disparia primavera, a new species of Notodontidae (Lepidoptera) from China - Saldaitis, Aidas; Ivinskis, Povilas; Rimsaite, Jolanta (Zootaxa, 2011)
The genus Disparia Nagano, 1916 contains 15 species from the Palaearctic which are best separated by male genitalia (see Schintlmeister, 2008). Disparia are distributed throughout Southeast Asia, especially China (Kobayashi, Kishida & Wang, 2003, 2005; Schintlmeister & Fang 2001; Schintlmeister 2007, 2008; Wu & Fang 2003). A. Floriani collected an unknown Disparia in April 2011 at light in Sichuan Province, China, and we describe it herein as new.